A Simple and Complete Supercapacitor Characterization System Using a Programmable Sourcemeter - José Henrique Alano; Lucas da Silva Rodrigues; Guilherme Kurz Maron; Bruno da Silveira Noremberg; Amanda Dantas de Oliveira; Oscar Paniz; Rubens Maribondo do Nascimento; Neftalí Lenin Villarreal Carreño (Orbital: The Electronic Journal of Chemistry, 2019)
The development of new materials and systems capable of storing energy efficiently with a fast power delivering has been the subject of several studies. Many techniques and instruments are used for the characterization of these systems. Some involve the use of electrochemical techniques, such as cyclic voltammetry and electrochemical impedance spectroscopy, while others use instruments specially developed for this purpose. In this study, we provide a simple and functional supercapacitor characterization system using a programmable sourcemeter with an embedded scripting language. For the validation of the system, commercial capacitors and supercapacitors devices based on activated carbon and manganese dioxide were used. In a few steps, the system is capable of efficiently determine the main parameters used in the characterization of supercapacitors, for instance, specific capacitance, specific energy density, specific power density and equivalent series resistance. From the data collected, the system can also determine the stability and performance of supercapacitors, which are fundamental parameters used in the development of new electrodes for energy storage devices.DOI: http://dx.doi.org/10.17807/orbital.v11i2.1374